Identifikasi dan Uji Ketahanan Cabai pada Tingkat Kematangan Buah Muda terhadap Penyakit Antraknose Colletotrichum acutatum Isolat Sukabumi - Neni Gunaeni; Eli Korlina; Redy Gaswanto (Universitas Muhammadiyah Purworejo, 2021)
One of the most dominant diseases that attack chili plants is anthracnose (Colletotrichum acutatum). This disease can affect fruit, both newly formed and ripe, causing considerable losses in quality and quantity of up to 20% - 90%. The aim of the study was to select chili varieties/lines at the maturity level of young (green) fruit that could potentially be resistant to anthracnose (C. acutatum) on a laboratory scale. The study was carried out at the Vegetable Crops Research Institute with an altitude of 1250 meters above sea level from July to September 2019. Samples of chilies infected with anthracnose were taken from chili plants in Sukabumi and identified using the PCR method to obtain C. acutatum isolates. The treatment that was tried was carried out on 26 chili lines/varieties at the maturity level of young fruit (green). Each treatment consisted of 5 chilies and 1 (one) control treatment (without anthracnose infection). The research design in this study was a completely randomized design that was repeated 3 (three) times. The results showed that: (1). morphological isolates appear white and gray, and cream, white, peach for the color of the colonies on the bottom. (2). Isolate of C. acutatum from Sukabumi was identified by PCR method of DNA band measuring 490 bp. (3). The results of inoculation of chili at the maturity level of young fruit (green) with isolates of C. acutatum from Sukabumi obtained resistant strains/varieties: 2A (R4) CB, 4A (R-15) B, 4B (R09) CB, 5A (R- 10) CB with lesion diameter less than 5 mm.